You could factor out a 7 to get
Answer:
c. (-2, 5)
Step-by-step explanation:
y - 2 = 3/2(x + 4)
to know which is the correct option we have to replace the equation x and y with what is in the point
a.
y - 2 = 3/2(x + 4)
(-1) - 2 = 3/2((-2) + 4)
-3 = 3/2(2)
-3 = 3
Wrong
b.
y - 2 = 3/2(x + 4)
(5) - 2 = 3/2((-6) + 4)
3 = 3/2(-2)
3 = -3
Wrong
c.
y - 2 = 3/2(x + 4)
(5) - 2 = 3/2((-2) + 4)
3 = 3/2(2)
3 = 3
Correct
d.
y - 2 = 3/2(x + 4)
(-1) - 2 = 3/2((6) + 4)
-3 = 3/2(10)
-3 = 15
Wrong
The correct answer is B. If you drop the parenthesis and collect like terms you get 8-3i.
Answer:
They help you see progressions but sometimes graphs can be manipulated to convey specific data and hide others like using methods called cherry picking, changing x and y axis and etc.